Addressing the links between and internal vs. external regulation factors, achievement emotions and gender in problematic use of ICT at university - de la Fuente, Jesús; Lecuona-López, Leyre; Pachón-Basallo, Mónica; San Martín-Íñiguez, Leyre; Blanco-Sarto, Pablo (Frontiers in Psychology, 2024)
Context The study of internal and external regulation in the use of Information and Communications Technology (ICT) and the analysis of academic emotions have become increasingly important due to their impact on academic life at university. Objectives This research aims to investigate the links between internal vs. external regulation factors, achievement emotions, and gender in the problematic use of ICT among university students. Methodology The study recruited 317 university students, predominantly female (72.51%), using an ex-post facto design. The SRT-ERT scale was used to assess technology-related behaviors, and the AEQ Scales measured academic emotions before, during, and after class. Correlation analysis, multiple regression analysis, and ANOVA were employed to identify significant relationships. Results Significant relationships were identified between regulatory behaviors, with male students exhibiting more dysregulated behavior and greater exposure to dysregulatory technology environments. Individual and contextual behavioral nonregulation and dysregulation in the use of ICT were significantly predictive of negative academic emotions. Conclusion The findings suggest that both personal and contextual factors of regulation significantly influence the emotional experiences of students in academic settings. The study highlights the need for psycho-educational interventions to promote better regulatory behaviors among university students, particularly males.